Chinese supply chain shocks - Makram Khalil; Marc-Daniel Weber (Deutsche Bundesbank, 2022)
In structural vector autoregressive models of United States and euro area manufacturing, we use sign restrictions to identify shocks that alter the frictions to Chinese supply chain trade. We find a quantitatively significant role of such shocks for the decline of US manufacturing output at the height of the Sino-American trade tensions in 2019. At the beginning of the Covid-19 pandemic in early 2020, the results pointed towards large spillovers from the shutdown in China to manufacturing in the US and the euro area. Moreover, for the recovery in late 2020 and 2021, favourable Chinese supply chain shocks related to the shift of preferences towards goods with a large China valued-added content played a relevant role. Interestingly, the impact of Chinese supply chain shocks is not limited to manufacturing sectors that are highly exposed to China. Furthermore, negative Chinese supply chain shocks cause upward price pressure across the whole manufacturing industry.
Keywords: E32; F41; F62; 330; Cross-border supply-chain disruptions; trade frictions; China; trade tensions; Covid-19 recession; US and euro area manufacturing